Pengaruh Kondisi Sosial Ekonomi Keluarga dan Lingkungan Teman Sebaya terhadap Minat Melanjutkan Pendidikan - Sitohang, Sasya; Rustiana, Ade; Nurdianti, Raden Roro Suci (Global Education Journal, 2023)
Research on the socio-economic conditions of the family and the environment of peers towards interest in continuing vocational and higher education has been carried out. Vocational education and higher levels nowadays must have skills that are very influential to the job position. This research aims to find out to what extent the socio-economic conditions of the family, the environment of peers influence the interests of continuing vocational education and higher levels of students of the Faculty of Education and Sciences of the University of Siliwangi Force 2019 both partially and simultaneously. This research uses quantitative research methods of the survey type. The population in this study is the entire student FKIP University of Siliwangi Force 2019 which consists of 10 majors as many as 1150 people. As for the sampling technique used, using Proptional Random Sampling of 288 people, to obtain a representative sample, taking subjects from each layer or each region equal to or proportional to the number of subject. Data collection techniques using questionnaires. The results of the study showed that: 1) the partial test results stated that the significant value of the socio-economic condition of the family is 0.054 meaning there is no influence between the social and economic conditions of the household and interest in continuing vocational education and higher levels, 2) the significant environmental value of peers is 0.005 meaning that there is influence among peer environments on the interest to continue vocational and higher level education, 3) simultaneously the significance value obtained is 0,000 meaning there are influences between social economic conditions and the environment of peer friends on interests of continuing professional education and the higher levels.